Experimental evidences for the fallacy of the STR version in the physics textbooks - Antonov, Alexander Alexandrovich (European Journal of Applied Sciences, 2021)
The article presents experimental proofs of falsity of the generally accepted version of the SRT studied in physics textbooks and truth of its alternative version. It is explained that the practical activity of radio engineers all over the world daily proves the principle of physical reality of imaginary numbers. Therefore, the postulate of not exceeding the speed of light was refuted actually even before the creation of SRT. And very complicated and expensive experiments OPERA and ICARUS in order to disprove this postulate of STR were not really necessary and are explained only by serious deficiencies in physics education, which ignores the need for knowledge of radio engineering. It is shown that if the generally accepted version of STR was true, then our world would be very different, because there would be no television, no mobile telephony, no radar, no GPS trackers, we would know neither the physical law of Ohm in Steinmetz interpretation, nor the physical phenomenon of resonance, we would hear neither bell ringing nor piano music, in nature there would be no tsunami, no ’Indian summer’ and much more. Even children’s swing wouldn’t sway after being pushed by parents. Therefore, it is concluded that the sections of physics textbooks related to relativistic physics, astronomy and astrophysics require correction.